2022
DOI: 10.3390/foods11244028
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Farming Systems, Genotype and Their Interaction on Bioactive Compound, Protein and Starch Content of Bread and Spelt Wheat

Abstract: An increase in the production and consumption of spelt products can be associated with positive effects on human health, which are attributed to bioactive compounds present in the grain. The basic success of spelt wheat in organic farming might be explained by the fact that spelt wheat belongs to the group of hulled wheat where the presence of a husk protects the seed from abiotic and biotic stress factors, thus demanding less chemical protection. The goal of this study was to investigate the variations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…On the other hand, under conditions of limited rainfall at the tillering stage and the beginning of stalk shooting, AR content in grain was similar at both fertilisation levels of 70 and 100 kg N•ha −1 . Takač et al [65], found that spelt wheat grain contained more alkylresorcinols in organic cultivation compared to conventional cultivation where increased mineral nitrogen fertilisation is applied.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, under conditions of limited rainfall at the tillering stage and the beginning of stalk shooting, AR content in grain was similar at both fertilisation levels of 70 and 100 kg N•ha −1 . Takač et al [65], found that spelt wheat grain contained more alkylresorcinols in organic cultivation compared to conventional cultivation where increased mineral nitrogen fertilisation is applied.…”
Section: Resultsmentioning
confidence: 99%
“…Derived profitability of spelt organic production is usually the result of obtained market price, where compared to common (bread) wheat its market price could be up to three times higher. Despite the more expressed energy efficiency, or health and environmental impact in organic agriculture (including the spelt production), (Smith et al, 2015;Takač et al, 2022) the negative side organic production arises from lower yields (Gabriel et al, 2013) that is commonly compensated by higher food-product's prices (Singh and Grover, 2011;Cristache et al, 2018).…”
Section: Economic Assessment Of Organic Spelt Productionmentioning
confidence: 99%
“…The determination of starch content was based on Takac et al [45], while the protein content was determined as described by Dong et al [46]. Both the content of starch and protein in root powder sample of sweet potato were evaluated by near infrared spectroscopy (NIRS) with a FOSS Analytical A/S (DS2500, FOSS Company, Hillerød, Denmark).…”
Section: Starch and Protein Determinationmentioning
confidence: 99%